2017
DOI: 10.1108/par-06-2016-0064
|View full text |Cite
|
Sign up to set email alerts
|

Measuring efficiency of Vietnamese banks

Abstract: Purpose This paper aims to examine alternative methods for treating nonperforming loans (NPLs) in bank cost-efficiency studies using stochastic frontier analysis (SFA). Design/methodology/approach The authors consider three methods of treating NPLs in SFA: as an additional control variable, as an environmental factor or as a deduction from total loans. Using data from the Vietnamese banking system (2003-2010), the authors then compare these results with those of the base model (where total loans is used rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…In particular, Stewart et al (2016) revealed that, in Vietnam, small and medium-sized banks were less efficient than large and very large banks, and the small banks had the lowest efficiency ratings. This was supported by Ngo and Tripe (2017) and Nguyen et al (2016) where they both found that SOCBs (which are large in size) were more (cost)-efficient than JSCBs (which are generally smaller). In terms of profit efficiency, findings from Vu and Nahm (2013) argued that Vietnamese banks operated well below the frontier in the 2000-2006 period mainly due to allocative inefficiency (of using labour, fixed assets , and deposits and other borrowed funds) rather than technical inefficiency.…”
Section: The Vietnamese Banking System and Its Efficiencymentioning
confidence: 80%
See 3 more Smart Citations
“…In particular, Stewart et al (2016) revealed that, in Vietnam, small and medium-sized banks were less efficient than large and very large banks, and the small banks had the lowest efficiency ratings. This was supported by Ngo and Tripe (2017) and Nguyen et al (2016) where they both found that SOCBs (which are large in size) were more (cost)-efficient than JSCBs (which are generally smaller). In terms of profit efficiency, findings from Vu and Nahm (2013) argued that Vietnamese banks operated well below the frontier in the 2000-2006 period mainly due to allocative inefficiency (of using labour, fixed assets , and deposits and other borrowed funds) rather than technical inefficiency.…”
Section: The Vietnamese Banking System and Its Efficiencymentioning
confidence: 80%
“…The following three years saw a moderate recovery, reaching 18.8% in 2015. The development of the Vietnamese banking industry and its performance has been examined by many studies, including market reports from international financial institutions (e.g., WB or IMF) as well as individual researchers (Ngo 2012;Ngo and Tripe 2017;Nguyen and Simioni 2015;Nguyen et al 2016;Stewart et al 2016). In particular, Stewart et al (2016) revealed that, in Vietnam, small and medium-sized banks were less efficient than large and very large banks, and the small banks had the lowest efficiency ratings.…”
Section: The Vietnamese Banking System and Its Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…This input represents the labour cost of the banking system, which is also common in the literature, except that studies on individual banks’ efficiency normally use the personnel expenses instead (Sathye, 2001; Avkiran, 2011; Chortareas et al , 2011). Meanwhile, we use the private credit to GDP ( Credit ) which accounts for the credit by commercial banks to the private sector as a share of GDP (as opposed to the variable of total loans which is commonly used to assess individual banks by Delis et al (2011) and Ngo and Tripe (2016, 2017), among others) as our first output. The second output is the NIM), accounting for the value of a bank’s net interest revenue as a share of its interest-bearing assets.…”
Section: The Empirical Models and Datamentioning
confidence: 99%